Cryogenic Noble Gas Separation without Distillation: The Effect of Carbon Surface Curvature on Adsorptive Separation - Kowalczyk, Piotr; Gauden, P.; Terzyk, A. (American Chemical Society, 2012)
Applying a novel self-consistent Feynman−Kleinert−Sesé variational approach (Sesé, L. M. Mol. Phys.1999, 97, 881−896) to quantum thermodynamics and the ideal adsorbed solution theory, we studied adsorption and equilibrium separation of 20Ne−4He mixtures in carbonaceous nanomaterials consisting of flat (graphite-like lamellar nanostructures) and curved (triply periodic minimal carbon surfaces) nanopores at 77 K. At the infinite mixture dilution, Schwarz P-carbon and Schoen G-carbon sample represents potentially efficient adsorbents for equilibrium separation of 20Ne−4He mixtures. The equilibrium selectivity of 20Ne over 4He (αNe−He) computed for Schwarz P-carbon and Schoen G-carbon sample is very high and reaches 219 and 163 at low pore loadings, respectively. Graphite-like lamellar nanostructures with interlamellar spacing (Δ) less than 0.6 nm are also potential adsorbents for equilibrium separation of 20Ne−4He mixtures at cryogenic temperatures. Here, αNe−He of 80 is predicted for Δ = 0.46 nm at low pore loadings. The quantum-corrected molar enthalpy of 20Ne adsorption strongly depends on the curvature of carbon nanopores.For Schwarz P-carbon sample, it reaches 8.2 kJ mol−1, whereas for graphite-like lamellar nanostructures the maximum enthalpy of 20Ne physisorption of 5.6 kJ mol−1 is predicted at low pore loadings. In great contrast, the quantum-corrected molar enthalpy of 4He adsorption is only slightly affected by the curvature of carbon nanopores. The maximum heat released during the 4He physisorption is 3.1 (Schwarz P-carbon) and 2.7 kJ mol−1 (graphite-like lamellar nanostructure consisting of the smallest flat carbon nanopores). Interestingly, for all studied carbonaceous nanomaterials consisting of curved/flat nanopores, αNe−He computed for the equimolar composition of 20Ne−4He gaseous phases is still very high at total mixture pressure up to 1 kPa. This circumstance is indicative of the possibility of carrying out the adsorption separation of 20Ne−4He mixtures at pt < 1 kPa and 77 K that do not require high-energy consumption. Presented potential models and simulation methods will further enhance the accuracy of modeling of confined inhomogeneous quantum fluids at finite temperatures.